Flesh firmness examination of scab-resistant apple varieties in a storage experiment - Orosz-Tóth, Mihály; Kincses, Sándorné (Acta Agraria Debreceniensis, 2020)
Of the different physical characteristics of fruits, one of the most essential qualities is flesh firmness, as is an important parameter when selling fresh apples, processing the fruit (processing industry) and during its storage. In the scope of our research, we examined five apple varieties originating from the Derecske horticultural site of KITE cPlc. in 2016. The plantation was planted to be suitable for intensive apple production. Samples were collected at the time of maturity (August-October) of the given variety. The five examined apple varieties (Gaia, Isaaq, Modí, Smeralda and Fujion) are all resistant to apple scab (fungal disease caused by Venturia inaequalis). The two-month storage experiment was conducted at 16-17 °C, which had an aggressive effect on our stored apples. Flesh firmness, weight and diameter were measured on three dates for each of the five apple varieties. Our results were evaluated using IBM SPSS Statistics 20 software. We aimed to compare flesh firmness, weight and diameter of the five apple varieties and their changes during storage. Isaaq (86.34 N/cm2), Modí (94.06 N/cm2) and Fujion (84.90 N/cm2) had outstanding initial flesh firmness results. The Modí apple variety provided the best storage parameters.